PARENTAL INVOLVEMENT AND ACADEMIC ACHIEVEMENT: A CRITICAL VIEW FROM EDUCATIONAL CORESPONSIBILITY - Ángela del Carmen Rusinque Troches; Myriam Mendivelso Prieto (DIALÉCTICA, 2026)
This essay critically analyzes how and under what conditions parental involvement influences academic performance from the perspective of shared educational responsibility, explaining its rationale in a context of recent declines in learning outcomes and reduced family involvement. Based on a synthesis of recent meta-analyses and comparative reports, as well as classic frameworks of family-school relationships (expectations, academic socialization, and bidirectional communication; the Hoover-Dempsey and Sandler models; and Epstein’s six types), it argues that parental involvement has positive but modest effects on performance: high and realistic expectations, academic socialization, and purposeful communication carry more weight than direct help with homework, the effect of which is inconsistent when it replaces student autonomy. It is not simply a matter of pooling efforts, but of recognizing that each stakeholder has an irreplaceable role in human development. In this sense, family involvement is not limited to completing school assignments, but rather involves being part of an educational community that educates through affection, active listening, and cooperation. Furthermore, the need for inclusive and flexible strategies that address barriers of time, connectivity and context is emphasized, promoting the quality of the family-school bond, highlighting that family support is not reduced to the quantity of activities, but to the quality time given to the child at home, which promotes sustainable learning.